Tingkat Kesadaran Terhadap Pelaksanaan Zakat Profesi (Studi Kasus Universitas Ibn Khaldun Bogor) - Irma Lailan; Ikhwan Hamdani; Syarifah Gustiawati (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
Zakat profession it self is one of the themes of contemporary jurisprudence that has not been fully accepted among Islamic scholars. Some circles still doubt even reject the validity of the withdrawal of profession zakat imposed on various professions